Art teaching in times of pandemic caused by COVID-19: challenges of teachers with remote education in southern Amazonas (Research, Society and Development, 2020)
This article aims to bring reflections on how Art teaching is occurring in times of pandemic caused by COVID-19, especially the challenges of art teachers with remote education in Lábrea, southern Amazonas. It is a qualitative research, developed with the Postgraduate Program in Teaching of Sciences and Humanities - PPGECH, from the Institute of Education, Agriculture and Environment - IEAA, from Universidade Federal do Amazonas - UFAM. The construction of the data took place through the application of an online questionnaire, produced in Google Forms, containing 20 questions (open and closed). The data were analyzed in the light of the Content Analysis defined by Bardin (2016). The results indicated that the challenges experienced by Art teachers in southern Amazonas are directly related to: a) the difficulty of accessing the internet; b) fragmentation in the teacher-student relationship; c) and the lack of teaching materials. Considering these findings, it is necessary to analyze the effectiveness of remote teaching and the poor quality of the internet signal in the context researched, presenting itself as limiting factors in the teaching and learning process. In view of this reality, it becomes urgent and necessary to think of strategies capable of supplying, or at least minimizing, the deficit related to the process, considering that there was a significant increase in the workload of the teacher and little effectiveness in the quality of Art teaching.